Magma Genesis and Arc Evolution at the Indochina Terrane Subduction: Petrological and Geochemical Constraints From the Volcanic Rocks in Wang Nam Khiao Area, Nakhon Ratchasima, Thailand - Hunyek, Vanachawan; Sutthirat, Chakkaphan; Fanka, Alongkot (Frontiers in Earth Science, 2020)
Volcanic rocks and associated dikes have been exposed in Wang Nam Khiao area, Nakhon Ratchasima Province, northeastern Thailand where complex tectonic setting was reported. These volcanic rocks are classified as rhyolite, dacite, and andesite while dikes are also characterized by andesitic composition. These dikes clearly cut into the volcanic rocks and Late Permian hornblende granite in the adjacent area. Rhyolite and dacite are composed of abundant plagioclase and quartz whereas andesite and andesitic dike contain mainly plagioclase and hornblende with minor quartz. The volcanic rocks typically show plagioclase and hornblende phenocrysts embedded in fine-grained quartz and glass groundmass whereas dike rocks contain less glass matrix with more albitic laths. P-T conditions of crystallization are estimated, on the basis of Al-in-hornblende geobarometry and hornblende geothermometry, at about 4.5 – 5.5 kbar, 861 – 927 oC and 4.8 – 5.5 kbar, 873 – 890 oC for the magma intrusions that fed volcanic rocks and andesitic dikes, respectively. Whole-rock geochemistry indicates that these rock suites are related to calc-alkaline hydrous magma. The enriched LILE (e.g. Rb, Sr) and depleted HFSE (e.g. Nb, Ce, Ti), with similar REE patterns indicate arc magmatism. The results of this study are comparable to the continental arc magmatism along the Loei Fold Belt as a consequence of the Late Permian Palaeo-Tethys subducted beneath Indochina Terrane.